China's policies on its borderlands and the international implications - Hao, Yufan; Chou, Bill K. P. (World Scientific Pub., 2011)
Examines the interplay of two sets of policies: the Chinese government's policies to its borderlands and international relations. This title argues that China's policymakers fail to make complete use of the opportunities in the borderlands for accomplishing foreign policymakers' agenda to strengthen China's relations with other countries.